Bubblewrapped: (Queered) Exhibition Making as a Means of Creating Spaces in Johannesburg Which Balance Intimacy, Safety and Access - Nyathi, Denzel (University of the Witwatersrand, Johannesburg, 2024)
While the exhibition, as perhaps the main tool of curating, is an excellent space for symbolic generation, I venture to draw close parallels to the internet, as a possible exhibition site of its own, to question how better the traditional art exhibition can be configured to make room for intimacy in the face of capitalism and its subsequent implications on how it is the contemporary Johannesburg art ecosystem operates and dictates professional interaction. It maintains the ever-relational position of contemporary curatorial practice, while complicating the issue of proximity (between disciplines and between people) even further by looking into what role controlling access plays in ensuring an intimate experience feels safe, and doesn’t border on being an experience which makes one feel unnecessarily vulnerable. The affective fine-tuning of this venture becomes a precarious task, which I undertake collaboratively with the interviewee respondents of this research. In consideration of these people and the overdetermination of the commercial sector in the Johannesburg art scene, the research report below asks the question of how it is that exhibition making can be reconfigured by the curator to work in more intimate ways to therefore make space for the various members involved in exhibition-making to feel a sense of safety and belonging in their work. bubblewrapped, as a queered exhibition, takes further this research and continues to think with the various practitioners in a public exhibition format, and thus continues to experiment with means of preserving intimacy
A research report Submitted in fulfillment of the requirements for a Master of Arts in Contemporary Curatorial Practice , In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: intimacy; paracuratorial; exhibition-making; affect; digital curation; alternative spaces; slow curating; queered; UCTD; SDG-16: Peace, justice and strong institutions; SDG-11: Sustainable cities and communities